On some issues of legal regulation of radiation safety from natural radionuclides in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
Work is executed within the framework ofproject «The study of radon oncology danger for population by measuring the vertical, horizontal and temporal topology of emanation and its accumulation in biological objects». The article examines the problems associated with the need to ensure the radiation safety of the population from natural radionuclides. Analyzes the basic regulations to address the problem. Noting the absence in practice for transactions of purchase and sale of real estate of any information about her background radiation. The authors present a proposal for the practical implementation of the requirements of the Radiation Safety Act.Key words: radiation safety, radon decay products, radiation monitoring, regulations, law.